Advances in Endophytic Research 2013
DOI: 10.1007/978-81-322-1575-2_6
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Dark Septate Endophyte Functions: Insights from the Arabidopsis Model

Abstract: The global occurrence of plant root-associated fungal endophytes and their great abundance in many habitats necessitate studies to decipher their potential functions. Improved understanding of the basic endophyte ecology including host range, host preference, and host responses to endophyte colonization has been made possible through populations of endophytes (e.g., Periconia macrospinosa and Microdochium sp.) isolated from North American native tallgrass prairie. The recent demonstration of the endophyte symb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 151 publications
(251 reference statements)
1
27
0
Order By: Relevance
“…It has been suggested that endophytic fungi can act symbiotically with plants, increasing the absorption of nutrients as well as the response to pathogens and stress conditions, which translates into gains in growth (Mandyam and Jumpponen, 2014). In this study, a linear temporal increase was observed for SL in all treatments.…”
Section: Discussionsupporting
confidence: 49%
“…It has been suggested that endophytic fungi can act symbiotically with plants, increasing the absorption of nutrients as well as the response to pathogens and stress conditions, which translates into gains in growth (Mandyam and Jumpponen, 2014). In this study, a linear temporal increase was observed for SL in all treatments.…”
Section: Discussionsupporting
confidence: 49%
“…Such endophytic bacteria colonize healthy plant tissues without causing any disease symptoms to the host plants. Endophytes have been regarded as the most prolific class of microorganisms that can help host plants to counteract the negative impacts of biotic and abiotic stress conditions [5,24]. Endophytic bacteria can be an alternative to chemical fertilizers as the use of bacterial endophytes has been practiced throughout the world to replace the use of chemical fertilizer [26].…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of biotic and abiotic drivers regulate the colonization rates of root fungal symbionts. For instance, root colonization rates by AMF and DSE differ among plant functional groups, with grasses in this montane ecosystem commonly supporting higher colonization of DSE relative to AMF, whereas forbs are typically more heavily colonized by AMF (Newsham , Mandyam and Jumpponen , Ranelli et al. ).…”
Section: Discussionmentioning
confidence: 94%
“…A wide variety of biotic and abiotic drivers regulate the colonization rates of root fungal symbionts. For instance, root colonization rates by AMF and DSE differ among plant functional groups, with grasses in this montane ecosystem commonly supporting higher colonization of DSE relative to AMF, whereas forbs are typically more heavily colonized by AMF (Newsham 2011, Mandyam and Jumpponen 2014, Ranelli et al 2015. Additionally, plant nutrient status and soil nutrient availability are strong determinates of fungal colonization rates (Bruce et al 1994, Johnson et al 2003, Egerton-Warburton et al 2007, Henning et al 2018.…”
Section: Drivers Of Fungal Colonization Patternsmentioning
confidence: 92%